2013
DOI: 10.1016/j.juro.2012.10.022
|View full text |Cite|
|
Sign up to set email alerts
|

Routine Urine Cytology has No Role in Hematuria Investigations

Abstract: Routine urine cytology is costly and of limited clinical value as a first line investigation for all patients with hematuria, and should be omitted from guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…There were 47 cancers in the present series, which was low. A larger series may suggest a small benefit for urinary cytology in patients with a normal cystoscopy and imaging, as previously reported by others . We acknowledge that urinary cytology may test positive because of a cancer anticipatory effect .…”
Section: Discussionsupporting
confidence: 73%
“…There were 47 cancers in the present series, which was low. A larger series may suggest a small benefit for urinary cytology in patients with a normal cystoscopy and imaging, as previously reported by others . We acknowledge that urinary cytology may test positive because of a cancer anticipatory effect .…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have shown that patients with hematuria do not require further workup because the NPV is very high (99.5%) and, generally, the clinical suspicion for malignancy is low . However, the lower NPV (90.1%) noted in patients with a history of UC suggests there are a significant number of FN findings.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract cytology (UTCy) was proposed as early as 1856 by Lambl as a clinically useful method with which to diagnose bladder cancer, and entered widespread use as a method with which to diagnose urothelial carcinoma (UC) after the seminal 1945 article by Papanicolaou and Marshall . Studies performed in the last 30 years have demonstrated that UTCy has a high sensitivity for the diagnosis of high‐grade urothelial carcinoma (HGUC) but a low sensitivity for low‐grade urothelial carcinoma (LGUC) . Voided urine (VU) specimens generally are used in the clinical setting of hematuria and persistent irritative voiding symptoms, whereas washing specimens, in conjunction with cystoscopy, are more commonly used in patients with a history of UC.…”
Section: Introductionmentioning
confidence: 99%
“…7 Urine cytology should not be used in primary care because of its low sensitivity; hence, a negative urine cytology result does not exclude malignancy. 8 There is unit-by-unit variation in the chosen modality of upper tract imaging, but usually ultrasound, CT or CT urography are utilised. Abnormalities are found in about 20% of patients, including bladder cancer (10.3%), kidney stones (8.4%), renal cell carcinoma (1.5%) and upper tract urothelial cancer (0.3%).…”
Section: Investigationsmentioning
confidence: 99%